Primary Leiomyosarcoma of the Thyroid; a Case Report and a Review of Recent Literature - Maysan Almegbe; Bushra Alahmadi; Kanaan Alshammari (Journal of Thyroid Cancer, 2023)
A case report of primary thyroid leiomyosarcoma with literature review. It discusses diagnostic pitfalls, histologic criteria, and management options.
Keywords: Leiomyosarcoma